Investigation of gene variation among non-alcoholic fatty liver disease patients in Gaza strip: a preliminary study - Al-Qatati, Abeer; Al-Beltaji, Ali; Alzaharna, Mazen (Universiti Kebangsaan Malaysia, 2023)
The prevalent hepatic presentation of the metabolic syndrome is a non-alcoholic fatty liver disease (NAFLD), one of the most common types of chronic liver illnesses. Patients with NAFLD may develop liver damage depending on their genetic heritage. In this preliminary study, our main aim was to detect the genetic association of p85α (Met326Ile), PNPLA3 (C>G), IL28B275 (A>G), and IL28B860 (C>T) single nucleotide polymorphisms (SNPs) with steatosis and NASH in patients from Gaza Strip. We performed an SNP analysis by RFLP-PCR in 33 cases of steatosis and 28 cases of non-alcoholic steatohepatitis (NASH), in addition to 29 age- and sex-matched controls. We found that only the mutant T allele of IL28B860 was significantly associated with an increased risk of steatosis (P = 0.04). The other studied alleles and genotypes were not significantly associated with increased or decreased risk of steatosis, NASH, or combined steatosis or NASH groups. Among all of the studied variables (age, sex, diabetes, and BMI), only BMI was significantly associated with an increased risk of steatosis as well as NASH. A linkage disequilibrium analysis showed that the association between the two SNPs of IL28B860 and IL28B275 was significant. Having the TG haplotype increased the risk of steatosis by 2.97 fold and the risk of combined steatosis or NASH by 2.44 fold. This haplotype increased the risk of NASH, but the effect was not significant.